355nm Wavelength Generation of Nd:YAG Laser Using Olive Oil - Fadhil, Aqeel S.; Al-Dergazly, Anwaar A.; Al-Dahan, Ziad T. (Al-Khwarizmi Engineering Journal, 2010)
This project introduces a prospective material for photonic laser applications. The material is olive oil which is classified as organic compound, having a good nonlinear optical properties candidate to be used in photonic applications. A high purity sample of olive oil has been used. The theoretical calculation to generate third harmonic wave using olive oil has been determine using MATLAB program. THG (λ=355nm) intensity has been determined at two cases of sample thicknesses 1mm and 10mm. The minimum threshold incident intensity to obtain THG intensity are equal Iω=7530 mW/cm2 at L=1mm and Iω= 6220 mW/cm2 at L=10mm. The possibility of generation of third harmonic in olive oil inside the cuvette has been experimented using different powers (90-120) mW of CW Nd:YAG laser. The signal of third harmonic generation has been detected using UV-340 Light Meter.